Lessons from an agricultural extension experiment in Mozambique: insights on teaching modalities and gender representation in extension and on productivity measurement - Kondylis, Florence; Mueller, Valerie (International Food Policy Research Institute, 2014)
Over the last seven years, the government of Mozambique has invested in rebuilding the agricultural extension network in the Zambezi valley, an area with high agricultural potential. These investments were in the form of increasing the supply of extension agents, providing them with housing, and building their capacity through training, among others. Our research team took advantage of this project to set up an experiment to rigorously examine the limitations in a ubiquitously practiced extension model, the Training and Visit model, and the importance of gender representation in extension to reach female farmers. In doing so, we also developed survey instruments to improve measures of agricultural productivity.